2016
DOI: 10.1093/toxsci/kfw192
|View full text |Cite
|
Sign up to set email alerts
|

Editor’s Highlight: Role of Spleen-Derived Macrophages in Ozone-Induced Lung Inflammation and Injury

Abstract: Macrophages and inflammatory mediators have been implicated in ozone toxicity. In these studies, we used splenectomized (SPX) mice to assess the contribution of splenic monocytes to pulmonary inflammation and injury induced by ozone. Cells and tissue were collected 24-72 h after exposure of mice to air or ozone (0.8 ppm, 3 h). Following ozone exposure, increased numbers of pro-inflammatory CD11b Ly6C and anti-inflammatory CD11b Ly6C monocytes were observed in spleens of control (CTL) mice. CD11b Ly6C and MMP-9… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
17
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 51 publications
2
17
0
Order By: Relevance
“…These results corroborate previous findings in a rat model of CPB [ 29 , 30 ]. Our findings did not show a significant increase in pulmonary macrophage infiltration, which is in concordance with previous work done by Francis et al [ 31 ] who found a significant increase in macrophage infiltration as late as 24–48 h after induction of lung injury. In future studies, longer follow up is planned to compare the macrophage activation to previous studies.…”
Section: Discussionsupporting
confidence: 94%
“…These results corroborate previous findings in a rat model of CPB [ 29 , 30 ]. Our findings did not show a significant increase in pulmonary macrophage infiltration, which is in concordance with previous work done by Francis et al [ 31 ] who found a significant increase in macrophage infiltration as late as 24–48 h after induction of lung injury. In future studies, longer follow up is planned to compare the macrophage activation to previous studies.…”
Section: Discussionsupporting
confidence: 94%
“…The spleen is necessary for the recruitment of classical monocytes and neutrophil extravasation into the injured lung. Both bone marrow and spleen are sites where monocytes can be recruited from in models of lung inflammation (30). We first set out to analyze classical monocytes in different compartments following lung IRI.…”
Section: Resultsmentioning
confidence: 99%
“…Both tissue compartments we analyzed are heterogeneous, which cannot be easily accounted for using bulk RNA-seq. Flow sorting or single-cell RNA-seq could be used to assign AM origin and phenotype, particularly after O3 exposure when inflammatory monocytes have been recruited from the periphery (FRANCIS et al 2017a;FRANCIS et al 2017b). Likewise, these approaches could be applied for the many cell types that comprise the airways and resident and/or recruited immune cell populations that are tightly associated with or interdigitated within the epithelium.…”
Section: Discussionmentioning
confidence: 99%